The Teachers' Strategies in Improving Islamic Religious Education Learning during the Pandemic at Nunggal Rejo State Elementary School - Citra Ayu Anggraini; Susi Nawanti; Muhammad Amir; Ghufron Faqih; Hendy Kurniawan; Ari Purnomo; Subandi; Indah Sari; Marwiyah; Siti Munawaroh (CV. Creative Tugu Pena, 2022)
The COVID-19 pandemic has significantly disrupted the learning process, requiring teachers to adapt in order to fulfill their roles as educators and mentors. Learning during the pandemic differs greatly from pre-pandemic methods, and teachers must choose appropriate strategies to ensure effective teaching continues. This study aims to explore the strategies employed by Islamic Education (PAI) teachers to enhance PAI learning during the pandemic at SDN 1 Nunggal Rejo, and to examine how the learning process was conducted during this period. This qualitative research was conducted at SDN 1 Nunggal Rejo using data collection techniques such as observation, interviews, and documentation. The data were collected, processed, and analyzed to draw conclusions. The findings indicate that teachers implemented several strategic approaches, including goal-oriented instruction, structured procedures, and clearly defined learning activities. Teachers acted as facilitators, and although discipline and time management were challenging, learning continued through a combination of online and limited face-to-face methods. Keywords: Teachers' Strategies, Enhance Learning Religious Education